Rasio Keuangan Dalam Memprediksi Financial Distress Pada Perusahaan Manufaktur Yang Terdaftar Di Jakarta Islamic Index - Husna, Husna Hayati; Muslina; Isra Maulina (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2024)
As one type of industry included in the Jakarta Islamic Index, the manufacturing industry is one of the companies that has a better level of economic stability compared to other types of companies. In addition, the manufacturing companies in JII increase the attractiveness for Muslim investors in investing. Information regarding the Company's financial condition is of concern to investors before making an investment. One of the important pieces of information that is the center of attention for a company is profit information. A review of the profits of manufacturing companies registered with JII shows a fluctuating trend and some have consistently decreased in the 3 years of observation. This condition will become increasingly severe and result in financial distress if early anticipation of the Company's financial condition is not carried out. To ensure this condition, this research was carried out to look at the financial distress conditions of manufacturing companies in JII. The analytical methods used are the Almant Z Score method and the Zmijewski method. This type of research is quantitative descriptive. The population is manufacturing companies registered with JII consecutively for 3 years and experiencing fluctuating and decreasing profit trends. The research sample consisted of seven companies. The results of the analysis using the Almant Z-Score model found that there were 3 companies in the Gray Area category of financial distress and 4 others in the safe category of financial distress. Meanwhile, the results of the analysis using the Zmijewski model show that the entire sample is in good financial health.